Illuminating Energy Efficiency: Satellite-Guided Insights for Optimizing Urban Street Lighting Across Indonesian Cities - Firman Afrianto; Dimas Tri Rendra Graha; Nuryantiningsih Pusporini; Alifianto Setiawan (Purnomo Yusgiantoro Center, 2025)
This study introduces a ground-breaking method for enhancing urban energy management by integrating high-resolution night-time satellite imagery from SDGSAT-1 with detailed ground-truth verification of street lighting across major cities in Central Java and DIY. Utilizing the Glimmer Imager for Urbanization (GIU) with 10-meter resolution, this research precisely identifies different urban street lamp types and evaluates their impact on energy consumption. As the demand for public street lighting grows with urban expansion, there is a pressing need for efficient energy management to sustain urban development and reduce environmental footprints. This study focuses on Semarang, Yogyakarta, and Solo, aiming to assess energy efficiency by examining how different street lighting affects energy usage across various road network types. By employing pan sharpening techniques to enhance image resolution and zonal statistics for in-depth analysis, the research finds significant correlations, especially in the red spectral band. This correlation suggests the potential of using SDGSAT-1 data to estimate streetlight energy consumption where direct measurements are unavailable. The findings also reveal significant variations in energy consumption across different road types, attributed to varying traffic and lighting needs. By highlighting these disparities, the study underscores the potential of transitioning to LED lighting, which can reduce energy consumption by up to 69%. This research not only demonstrates the capabilities of satellite imagery in urban energy management but also offers practical insights for cities looking to improve lighting efficiency, reduce costs, and promote sustainability in urban planning.